2019
DOI: 10.1021/acs.est.9b03386
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Adsorption Isotherms for Amphiphilic Surfactants in PM1 Aerosols from Different Regions of Europe

Abstract: Predicting the activation of sub-micron particles into cloud droplets in the atmosphere remains a challenge. The importance of surface tension,  (mN/m), in these processes has been evidenced by several works but information on the "surfactants" lowering  for atmospheric particles remains scarce. In this work, PM1 aerosols from urban, coastal and remote regions of Europe (Lyon, France, Rogoznica, Croatia, and Pallas, Finland, respectively) were investigated and found to contain amphiphilic surfactants in conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…The surface monolayer model predictions suggest surfactant concentrations on the order of several tens to 100 mM, consistent with reported atmospheric concentrations, are required to substantially affect N d (i.e., modify SS c by >20%). These predictions highlight the necessity of a more comprehensive understanding of the types and concentrations of surfactants in aerosol, as to date only a few studies in a few environments have been reported (7,8,10,29,46,47). Global simulations of N d have only rarely incorporated such surface partitioning models (5,6), in part because partitioning effects had not been experimentally confirmed until this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface monolayer model predictions suggest surfactant concentrations on the order of several tens to 100 mM, consistent with reported atmospheric concentrations, are required to substantially affect N d (i.e., modify SS c by >20%). These predictions highlight the necessity of a more comprehensive understanding of the types and concentrations of surfactants in aerosol, as to date only a few studies in a few environments have been reported (7,8,10,29,46,47). Global simulations of N d have only rarely incorporated such surface partitioning models (5,6), in part because partitioning effects had not been experimentally confirmed until this work.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the monolayer partitioning model predictions suggest that the total surfactant concentration in particles must be at least on the order of several tens to 100 mM for there to be a substantial effect on cloud droplet activation. Gérard et al (7,29) recently reported total surfactant concentrations in collected ambient fine aerosol reaching several tens to hundreds millimolar across Europe. Moreover, surfactant concentrations are enhanced in smaller (<200-nm diameter) atmospheric particles (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even when we consider the best agreement, the maximum difference in obtained LWC between CAS and FSSP could still be about 40 %. In addition, we suggest the deployment of another LWC sensor, e.g., the particle volume monitor (PVM-100; Gerber, 1999), during future campaigns in order to obtain another reference LWC value for intercomparison in a wide temperature range. In addition, we are continuously pursuing the development of a new generation of counters designed for ground-based in situ cloud measurements.…”
Section: Intercomparison Of Cas and Fssp -Derived Parameters Lwc Ed mentioning
confidence: 99%
“…He stated that FSSP can be regarded as an excellent microphysical sensor in continental, stratiform or cumuliform clouds with mostly small drops; however he noticed some discrepancies in the liquid water content, especially when cloud droplets larger than 25 µm were considered. Gerber et al (1999) performed and evaluated ground-based measurements of liquid water content using also an FSSP and a particle volume monitor (PVM). They observed large discrepancies too and stated that the FSSP overestimated liquid water content for large cloud droplets due to the inertial concentration effect.…”
Section: Introductionmentioning
confidence: 99%